Cortiça e tecnologias digitais: possibilidades de aplicação na Arquitectura efémera - Rafael Barros dos Santos (2017)
Cork and Digital Technologies: Possibilities of application in Ephemeral Architecture Cork, digital technologies and ephemeral architecture are the focus of this dissertation which are developed in two parts, study and theoretical investigation of themes and its intersecting lines, and last, in the presentation of a methodology and the elaboration of an ephemeral project applicating digital technologies in cork. This study explores cork as a material that has gained great impact in architecture over the last 20 years, by taking advantage of its intrinsic, performative and aesthetic characteristics and its great potential for out of the box applications. Having said that, this investigation revolves around how digital technologies interfere in the drawing and materialisation of the project and gives emphasis to the comprehension of the drawing's potential and digital fabrication in terms of geometric and aesthetic aspects of cork. At last, this dissertation reflects upon ephemeral architecture and its characteristics showing that it is an experimentation territory and a privileged work field for the development of innovative solutions using cork. As a conclusion, the growing interest in the integration of drawing tools and digital fabrication in the development of new applications and solutions for cork, as the characterizing project material have motivated a profound study and comprehension of its continuous relation with architecture. With the extensive study, this dissertation presents herself as a practical experience which relates all the themes mentioned earlier with the goal of analysing future opportunities for digital innovation in ephemeral architecture and simultaneously a bigger proximity between the architect and the entire development process of the project.